Le nahualli-tlahuipuchtli dans le monde nahuatl - Roberto Martínez González (Journal de la Société des Américanistes)
The nahualli-tlahuipuchtli in the nahuatl world. One of the least known characters in Lopez Austin’s (1967) article « Forty magician classes in the nahuatl world », is the tlahuipuchtli, a name given actually to some kind of bloodsucking witches. The goal in this work is to define the meaning and function of the belief in this kind of supernatural beings. If we consider that the sixteenth century sources do not present an exhaustive description of this supernatural character, then we must compare the ancient information with recent ethnographic data in order to explain and define its meaning. In the first part of the article, we review the ancient data; secondly we attempt to define the contemporary stereotype of the tlahuipuchtli and then describe how the Spaniard witchcraft concepts participated in the construction of modern tlahuipuchtli image. In the last section of this work, we define its symbolism in order to evaluate if the belief in bloodsucking witches existed in pre-hispanic times.